Comparative study of hypoglycemic effects of oral vildagliptin and voglibose on fasting blood sugar level in albino rats - Kumar, Mukesh; Kumar, Mukesh; Chandra, Akash; Keshri, Uma Shankar Prasad; Kumar, Rajiv (International Journal of Research in Medical Sciences, 2021)
Background: Diabetes mellitus is a metabolic disorder in which there is increased blood sugar level, glycosuria, dyslipidemia and sometimes ketonemia occurs. Increased blood sugar level leads to characteristic symptoms such as polydipsia, polyurea, blurring of vision, polyphagia and weight loss. Methods: Healthy male Wister rats weighing between 150-250 gm were taken. Total 2 groups A and B were prepared and each group contains 6 animals. Group A was administered voglibose as 0.6 mg/70 kg body weight. Group B was administered vildagliptin as 100 mg/70 kg body weight. Diabetes was induced in group A and B by administration of 120 mg/kg body weight of nicotinamide and 60 mg/kg body weight of streptozocin intraperitoneally. Streptozocin was administered after 15-20 minutes of administration of nicotinamide. After 72 hours of streptozotocin injection, fasting blood glucose level was determined and induction of diabetes was confirmed. The fasting blood samples were collected from all the groups on further days 7, 14, 21 and 28 day to determine the glucose level by glucometer. Results: The decline in fasting blood sugar level by voglibose was 36.4% on day 7, 40.2% on day 14, 43.94% on day 21 and 46.4% on day 28. The reduction in Fasting blood sugar level by vildagliptin was 49% on day 7, 52.25% on day 14 and 54% on day 21 and 28. Thus in group B rats, decline was maximal on day 7 and little fall was recorded on subsequent days. It suggests good efficacy as vildagliptin normalized the blood glucose level effectively. Conclusions: Vildagliptin was found significantly more effective in lowering fasting blood glucose level than voglibose.